MicroRNA-Mediated Gene Regulation of Secondary Metabolism in Plants. (2nd November 2021) - Jiang, Shan; Cui, Jin-Long; Li, Xiao-ke
Abstract: Plant microRNAs (miRNAs), a class of about 21-nucleotide-long small noncoding RNAs (ncRNAs), generally act as key regulators of their target genes by guiding mRNA cleavage or translational repression. Recent researches have reported that miRNAs can interact with pathway-related structural genes, transcription factors (TFs) and noncoding RNAs (ncRNAs) to form regulatory network in secondary metabolite (SM) biosynthetic pathways. The validated interactions can better reflect the real regulatory mechanism of miRNA and convert miRNAs into more efficient tools to control the production of precious SMs. However, there is no systematic review available on this topic especially in plants, particularly model plants and crops. Here, we firstly overviewed the critical secondary metabolic pathways in plants, especially those biosynthetic pathways related structural genes which were well-studied and representative SMs, including phenylpropanoids, terpenoids, alkaloids. Principally, we summarized miRNAs involved in the biosynthesis of SMs, miRNA-target modules and their regulation on the mentioned pathways in the last decade. Significantly, the modules included miRNA-structural gene, miRNA-TF, miRNA-ncRNA interaction pairs carried out by target validation or functional confirmation. This knowledge will promote understanding the sophisticated miRNA-mediated gene regulatory network of SM biosynthesis, and drive the development of synthetic biology.